Indonesia’s Halal Food Industry: Development and Challenges in Achieving Global Hub Status - Muawanah; Fauziah, Nur Dinah; Irna Zukhrufa Ainia; Dinda Tanti Sari; Fadlulloh, M. Yusuf (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The global halal industry has experienced significant expansion, driven by increasing Muslim consumer demand and the growing recognition of halal products beyond religious boundaries. Despite possessing the world’s largest Muslim population, Indonesia has yet to fully capitalize on its potential as a leading global halal food hub. This study aims to critically assess the development trajectory and key challenges of Indonesia’s halal food industry in the context of global competition. This research employs a qualitative library-based approach by systematically reviewing academic literature, industry reports, and policy documents published between 2015 and 2024. The analysis is conducted using a thematic approach to identify patterns in industry development, regulatory frameworks, and structural constraints affecting Indonesia’s positioning in the global halal market. The findings indicate that while Indonesia’s halal food sector has shown consistent growth and contributes positively to national economic performance, its global competitiveness remains constrained by several structural and institutional factors. These include fragmented halal certification systems, the absence of universally recognized global standards, limited strategic focus in product development, low levels of halal awareness among domestic stakeholders, and insufficient integration of Islamic financial instruments to support industry expansion. Furthermore, the study reveals that regulatory complexity and institutional dualism weaken governance effectiveness and reduce international trust. This study contributes to the literature by offering an integrative analytical framework that links regulatory, institutional, and market-driven challenges in the halal food industry, highlighting the gap between Indonesia’s demographic potential and its global competitiveness. The findings provide strategic insights for policymakers and industry stakeholders to strengthen Indonesia’s positioning as a global halal hub through regulatory harmonization, institutional consolidation, and enhanced ecosystem integration.